Treatment of Exchange Rate Issues in Bilateral Surveillance : A Stocktaking. (Policy Papers; Policy Paper, 2006)
Review the quality of the Fund staff's analysis and policy advice on exchange rate issues. The Fund is sometimes criticized for not taking a sufficiently clear position on several exchange rate issues, ranging from the assessment of the level of exchange rates to the description of exchange rate policies, and their adequacy. Is this criticism valid, and in what respect? Answering these questions is critical as exchange rate issues are at the heart of the Fund's surveillance mandate.